Respuesta :
6x² - 7x - 3 = 0 (Hence, factor)
6x² - 9x + 2x - 3 = 0
3x(2x - 3) + (2x - 3) = 0
(3x + 1)(2x - 3) = 0
Hence, (a) is correct.
6x² - 9x + 2x - 3 = 0
3x(2x - 3) + (2x - 3) = 0
(3x + 1)(2x - 3) = 0
Hence, (a) is correct.
Answer:
a.(2x - 3)
Step-by-step explanation:
Let's factorize 6x^2 - 7x - 3
First add and substract 2x
6x^2 - 7x - 3 + 2x - 2x
6x^2 - 9x + 2x -3
Then, take 3x as a common factor between the first and second term
3x*(2x - 3) + (2x -3)
Finally, take (2x -3) as common factor
(2x -3)*(3x +1)
So, both(2x -3) and (3x +1) are factors of 6x^2 - 7x - 3